Painting the Future: Leveraging Generative AI’s Power in the Financial Ecosystem - Hady, Abdel (Journal of Global Economy, Business and Finance, 2024)
Generative Artificial Intelligence (GenAI) stands out as a transformative force reshaping how institutions operate and innovate. This whitepaper traces the historical evolution of GenAI from conceptual stages to its current significance, highlighting key milestones and applications in the financial sector. Presently, GenAI is integrated into banking, particularly for fraud detection and personalized marketing. The case studies exemplify successful implementations by institutions like J. P Morgan and Microsoft showcasing benefits such as reduced fraud levels and improved customer experiences. The paper delves into the specific use cases across loan processing, portfolio management, asset management, regulatory compliance, and customer service automation. Despite GenAI's potential, the implementation and integration raise challenges related to data privacy, bias, ethical concerns, and technical complexities. The paper stresses the need for governance frameworks and compliance with global standards to tackle challenges. It recommends financial institutions prepare for future advancements by establishing efficient data pipelines, leveraging the cloud, building on existing frameworks, and adopting a human - led, tech - powered approach. It summarizes the critical importance of responsible innovation, urging institutions to embrace GenAI ethically to contribute to a more inclusive and sustainable financial ecosystem.